Prevalence of stuttering among school age children in Dakshina Kannada district of Karnataka, India - Aiswarya Liz Varghese; Palak Devani; Lakshmi Kunnath; Radish Kumar Balasubramanium; Gagan Bajaj; Sudhin Karuppali; Unnikrishnan Bhaskaran (Elsevier, 2023)
Purpose: Stuttering is a fluency disorder with a worldwide prevalence of 1%. Reports on the epidemiology of stuttering in India is limited. Our primary goal was to examine the prevalence of the disorder among school children. The study also aimed to study the impact of several risk factors on the prevalence of stuttering. Method: A total of 3437 children in the age range of 6-15 years were screened in 16 camps conducted in and around schools of Dakshina Kannada. The children were screened for stuttering using a screening tool by an SLP based on their grade and medium of instruction and further validated using Stuttering Severity Instrument-4. Result: The prevalence of stuttering in school going children was 1.68%. Gaussian test reveals effect of gender on the prevalence of stuttering (Z1 = 3.501, p < 0.001) with a ratio of 2.4:1 among males and females respectively. No significant association was obtained for socioeconomic status (X22 = 1.42, p = 0.492) and linguistic structure (Z1=1.653, p = 0.0984) on the prevalence of stuttering. Good to excellent inter-rater and intra-rater reliability was obtained. Conclusion: The prevalence of stuttering in Dakshina Kannada is established for the first time in the current study which helped determine in early identification and intervention for children with stuttering leading to better prognosis and quality of life.